2022
DOI: 10.1111/ecc.13600
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of coronavirus anxiety and caregiving burden among the parents of children with cancer during the COVID‐19 outbreak: A descriptive and cross‐sectional study

Abstract: Objective This study aimed to investigate the coronavirus anxiety and caregiving burden of parents of children with cancer during the COVID‐19 outbreak. Methods This descriptive and cross‐sectional study, including 136 parents of children with cancer, was administered through an online survey at a university hospital from 1 to 31 January 2021. Participants completed a questionnaire form, the Zarit Caregiver Burden Scale and the Coronavirus Anxiety Scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Children with chronic illness and cystic fibrosis who were thought to have risks of developing psychosocial problems during the pandemic were also not significantly affected. 33 34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with chronic illness and cystic fibrosis who were thought to have risks of developing psychosocial problems during the pandemic were also not significantly affected. 33 34…”
Section: Discussionmentioning
confidence: 99%
“…Children with chronic illness and cystic fibrosis who were thought to have risks of developing psychosocial problems during the pandemic were also not significantly affected. 33,34 In addition, more than half of our patients (58.3%) undergoing treatment lived in temporary housing such as rentals and boarding home for childhood cancer patients. The boarding home for childhood cancer patients helped establish a community of patients and their guardians for mutual support.…”
Section: Lifestyle Changes During the Pandemicmentioning
confidence: 99%
“…These losses could have heightened their perception of strain and their negative emotions, particularly in conjunction with the lack of in-person support they were able to receive due to physical distancing and lockdown mandates. Other studies of cancer caregiving during the pandemic also demonstrated that pandemic-induced social isolation and other psychological pressures may have negatively affected caregivers’ well-being [ 19 , 44 , 45 ]. This impact may be particularly salient for EYACs, as they are at higher risk for developing psychopathology, such as anxiety and depression [ 14 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that EYACs’ disappointment with medical care options during the pandemic may have cascading implications for their long-term grief adjustment, propensity for post-loss psychological growth, and broader attitudes about healthcare systems [ 46 ]. For example, pandemic restrictions limited many of the communication tools palliative care clinicians employ to help family members prepare for bereavement, such as in-person family meetings and end-of-life conversations at the bedside [ 44 ]. Their absence, along with the inability to hold remembrance services that provide comfort and opportunities for EYACs to receive support, likely increased their risk of experiencing complicated grief responses [ 47 ] and possibly promoted pessimism about navigating future caregiving or health circumstances.…”
Section: Discussionmentioning
confidence: 99%